ANALYSIS OF CONTRACTS AND LEGAL RESPONSIBILITIES IN DIGITAL AFFILIATE MARKETING SYSTEMS - Muhammad Khoirun Nizam (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2026)
The rapid development of digital technology has transformed commercial systems and legal relationships, including the emergence of digital affiliate marketing as a performance-based marketing model. In this system, affiliates promote products or services through digital platforms and receive commissions based on successful transactions. Despite its efficiency, affiliate marketing raises legal and ethical issues such as unclear contractual agreements, misleading promotions, and potential consumer harm. This study aims to analyze the contractual framework and legal responsibilities of merchants, affiliates, and digital platforms from the perspectives of Indonesian positive law and Islamic economic law. Using a normative analytical method, the study examines legal regulations, Islamic legal doctrines, and digital marketing practices related to affiliate systems. The findings show that affiliate marketing practices can be categorized into juʿālah and wakālah bil ujrah contracts, which are valid as long as they fulfill the principles of transparency, fairness, and accountability. Merchants are responsible for product accuracy and commission payments, affiliates must provide honest promotions, and digital platforms must ensure transparent tracking systems and dispute resolution mechanisms. The study also finds that practices involving deception, misinformation, or unclear commission systems contradict the principles of maqāṣid al-sharī‘ah, particularly the protection of property (hifẓ al-māl) and individual rights (hifẓ al-nafs). Therefore, clear contractual terms, ethical promotion standards, and transparent digital systems are essential to create a fair and Sharia-compliant affiliate marketing ecosystem.